2017
DOI: 10.1007/s00268-017-4289-8
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes for Esophageal Squamous Cell Carcinoma Treated with Curative Intent in a Western Cohort: Should Multimodal Therapy Be the Gold Standard?

Abstract: This study provides evidence, consistent with CROSS data, that multimodal therapy for SCC can provide excellent outcomes with respect to overall survival, pathologic complete response rates, R0 resections and treatment-related mortality. A large RCT with specific arms for multimodal, dCRT and surgery alone is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The inclusion criteria were met by 35 articles describing 32 studies (21 Western and 11 Asian; Fig. 1) [7, 13, 14, 17–48]. Of the 35 articles included, two were RCTs and 33 were observational.…”
Section: Resultsmentioning
confidence: 99%
“…The inclusion criteria were met by 35 articles describing 32 studies (21 Western and 11 Asian; Fig. 1) [7, 13, 14, 17–48]. Of the 35 articles included, two were RCTs and 33 were observational.…”
Section: Resultsmentioning
confidence: 99%
“…The poor 5-year OS reported in this study is not exclusive to Brazil, as similar outcomes have been reported in other observational studies. 22 , 23 Along this line, Chen et al 24 reported a 5-year OS of 20% for patients with locally advanced ESCC treated with dCRT. Similar outcomes have been reported by the WECC esophageal study group, with a 5-year OS of 30% in patients with clinical stage II and III ESCC.…”
Section: Discussionmentioning
confidence: 97%
“…For FLOT, rates of pCR were variable, with one study reporting 0 and a prospective Italian study reporting rates of 7% [5, 6]. Real-world studies report pCR ranging from 32% to 43% for CROSS, though these include squamous cell carcinoma which is more likely to achieve a pCR [5‒8, 9].…”
Section: Discussionmentioning
confidence: 99%